Transparency of Costs and Competence of Village Apparatus Towards the Quality of Village Financial Reports (Study on Villages in Boalemo Regency, Gorontalo Province) - Abdullah, Muhamad Rifandi; Blongkod, Harun; Pakaya, Lukman (International Journal of Economics Studies, 2025)
This study examines the effect of cost transparency and the competence of village apparatus on the quality of village financial reports, focusing on villages in Boalemo Regency, Gorontalo Province. The research employs a quantitative method, using primary data collected through questionnaires with Likert scale measurements. A total of 117 respondents from various sub-districts in Boalemo Regency were selected using a saturated sampling technique. The data analysis was conducted using Structural Equation Modeling (SEM), processed through the AMOS 24 software. The results of the study indicate that cost transparency does not have a significant effect on the quality of village financial reports. However, the competence of village officials has a positive and significant impact on the quality of the reports. Furthermore, when considered together, both cost transparency and village apparatus competence contribute positively and significantly to the quality of village financial reports, as evidenced by an R-squared value of 71.9%. The remaining 28.1% of the variation in financial report quality is influenced by factors not included in this research model. The study is supervised by Mr. Harun Blongkod, S.Pd., Ak., M.SA as supervisor I, and Lukman Pakaya, S.Pd., MSA as supervisor II, in the Accounting Study Program, Department of Accounting, Faculty of Economics and Business, Gorontalo State University.